دراسة تأثير أشكال الكمون المتبادل على الضغط والطاقة الداخلية لبلورة الأرغون عند درجات الحرارة العالية (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2016)
This work is assigned to study the influence of different interaction potential forms on the pressure and internal energy of crystalline argon along its isothermal curves at high temperatures, expanded from melting point temperature up to room temperature at different molar volume values expanded up to its value, corresponded experimental equilibrium curves with gaseous and liquid phases within the framework of quasi-classical approximation. The pair-wise inter-atomic forces in conjunction with three-body forces were taken into consideration. The results of this study regarding the pressure and internal energy of crystalline Argon were compared with available experimental data. The comparison clearly indicates that the calculated results coincide well with the experimental results.يتناول هذا البحث دراسة تأثير الأشكال المختلفة لكمون التأثير المتبادل بين الذرات على الضغط والطاقة الداخلية لبلورات الأرغون على امتداد المنحنيات الإيزوحرارية الموافقة لدرجات الحرارة العالية الممتدة من درجة حرارة الانصهار حتى درجة حرارة الغرفة من أجل قيم مختلفة لحجم البلورة المولي تصل حتى قيمته الموافقة لمنحنيات التوازن التجريبية مع الطورين الغازي والسائل وضمن حدود تطبيق التقريب شبه التقليدي. و تأخذ هذه الدراسة بعين الاعتبار قوى التأثير المتبادل الثنائية و قوى التأثير المتبادل الثلاثية. وتقارن نتائج هذه الدراسة المتعلقة بالضغط والطاقة الداخلية لبلورة الأرغون مع المعطيات التجريبية المتوفرة حيث تشير المقارنة بوضوح إلى توافق نتائج الدراسة مع النتائج التجريبية.